تأثير استخدام الجدار الخازن للحرارة المزود بشبكة مائية على أحمال التبريد في المبنى - رامي جورج; سلفانا جنبلاط (Tishreen University, 2018)
The research is a software study and an experimental practical study to study the effect of the use of the heat storage wall with a water pipe network on cooling loads in the buildings, which in turn reduces the consumption of conventional energy and improves the sense of thermal comfort of the residents in construction, In the climatic conditions of Lattakia. The software study showed  by using simulation program TRNSYS ,the best direction for the heat storage wall is the south direction,  As the flow of water within the pipe network increases, the total cooling load drops, and we gain an increasing the saving ratio by 3[%] when increasing the flow from 30[L/h.m2] to 110[L/h.m2]. The total cooling load decreases as the pipe spacing is lower, so the optimum value of the spacing is 0.1[m] by saving ratio 50[%]. The research showed that the optimum value of the external diameter of the pipes is 0.02[m] , and the saving ratio is 52.6% . As the external diameter increases, the increase in the saving ratio becomes less than 0.5% and we get a better saving ratio when the temperature of the water entering the pipes decrease. The research showed that the use of the heat storage wall with a water network led to a decrease in the temperature of the internal air clearly, which provides a feeling of comfort for the residents of the building. The experimental practical study showed a approximate match of the results obtained through the software study when using the program, and confirmed the low internal air temperature clearly, which in turn leads to a decrease in total cooling load. نقدم في هذا البحث دراسة برمجية  وتجريبية لتأثير استخدام الجدار الخازن للحرارة المزود بشبكة مائية على أحمال التبريد في المباني، والذي يؤدي بدوره إلى ترشيد استهلاك الطاقة التقليدية، وتحسين الشعور بالراحة الحرارية للقاطنين في البناء، عند الشروط المناخية لمدينة اللاذقية. أظهرت الدراسة البرمجية عن طريق برنامج المحاكاة TRNSYS، أن أفضل توضع للجدار الخازن للحرارة هو اتجاه الجنوب، وأنه مع زيادة تدفق الماء ضمن شبكة الأنابيب ينخفض حمل التبريد الكلي، حيث وصلت الزيادة في نسبة التوفير 3[%] عند زيادة التدفق من [L/h.m2] 30 إلى [L/h.m2] 110. ووجدنا أيضاً أن حمل التبريد الكلي ينخفض كلما كان التباعد بين الأنابيب أقل، وتبين أن القيمة المثلى للتباعد هي 0.1[m] بنسبة توفير 50[%]. كما أظهر البحث أن القيمة المثلى للقطر الخارجي للأنابيب هي 0.02[m]، وتكون نسبة التوفير 52.6[%]، حيث مع زيادة القطر الخارجي عن هذه قيمة يصبح مقدار الزيادة في نسبة التوفير أقل من 0.5[%]. ونحصل على نسبة توفير أفضل عند انخفاض درجة حرارة دخول الماء إلى الأنابيب. أظهر البحث أن استخدام الجدار الخازن للحرارة المزود بشبكة مائية أدى إلى انخفاض في درجة حرارة الهواء الداخلية بشكل واضح، مما يؤمن الشعور بالراحة للقاطنين في البناء. أظهرت الدراسة التجريبية العملية تطابق تقريبي للنتائج التي تم الحصول عليها من خلال الدراسة البرمجية عند استخدام برنامج TRNSYS، وأكدت على انخفاض درجة حرارة الهواء الداخلية بشكل واضح، وهذا بدوره يؤدي إلى انخفاض حمل التبريد الكلي.